Service-learning experiences and outcomes in developing employability skills among TVET students in a public university in Malaysia - Mohd Zaid, Mohd Fakhrul Azizie (2020)
The need to develop future graduates that encompass employability skills has become one of the agendas in the Malaysian Educational Blueprint for Higher Education 2015- 2025. Hence, to rectify the aim, service-learning (SL) is introduced as among the strategies in promoting students with hands-on experience linked to the community engagement. Notably, the application of SL is limited despite evidences of volunteerism found in many scholarly works. SL transmits academic knowledge through volunteering works and is highly regarded as a foundation in developing students’ employability skills. Therefore, this study was conducted to explore the SL experiences and the outcomes in developing employability skills among TVET students in a Malaysian public university. Specifically, two research questions were formulated (i) what the students learned from their SL experience? and (ii) how SL project strengthen student employability skills? This study employed a qualitative case study approach to answer the research questions. The subjects of the study were purposely selected among second and third-year students in Bachelor of Education. The subjects of the study were chosen based on the criterion-based selection to ensure the rich information given by the informants. A total of four focus group discussions were conducted using semi-structured interview questions. This study utilised the Nvivo 12.0, a computerised software tool to organise and facilitate the data especially in the process of thematic analysis. The themes emerged based on students’ involvement in SL project were managing conflicts, knowledge-sharing and selfvalues. Meanwhile, four themes emerged concerning students’ employability skills development that are leadership skills, communication skills, critical thinking skills and teamwork skills. Based on the findings, SL able to be one of the subjective teaching practices for providing meaningful learning experience to students surrounded with community, which subsequently nurtured students’ employability skills including their career readiness for future job market.